The Dissolution of Olivine Added to Soil at 4°C: Implications for Enhanced Weathering in Cold Regions - Pogge von Strandmann, Philip A. E.; Tooley, Chloe; Mulders, Josephina J. P. A.; Renforth, Phil (Frontiers in Climate, 2022)
Crushed olivine was added to a core to mimic enhanced weathering, and water was continually dripped through for 6 months. Our experiments were conducted at 4°C, and are compared to previously run identical experiments at 19°C. Olivine dissolution rates in both experiments start out similar, likely due to fines and sharp crystal corners. However, after >100 days of reaction, the dissolution rate at 4°C was two orders of magnitude lower than at 19°C. The accumulation of heavy metals, such as Ni and Cd, was low in both experiments, but soil retention of these elements was proportionally higher at higher temperatures, likely due to enhanced sorption and formation of clays. Overall, this study suggests that olivine dissolution rates in experiments that mimic natural settings are orders of magnitude slower than in normal laboratory experiments, and that enhanced weathering may be a considerably less efficient method of carbon dioxide removal at low climatic temperatures. Both of these conclusions have implications for the application of enhanced weathering as a CO2 removal method.